2013
DOI: 10.1136/bmjopen-2013-002628
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying in the UK NHS: a questionnaire and interview study on prevalence, impact and barriers to reporting

Abstract: ObjectivesTo examine the prevalence and impact of bullying behaviours between staff in the National Health Service (NHS) workplace, and to explore the barriers to reporting bullying.DesignCross-sectional questionnaire and semi-structured interview.Setting7 NHS trusts in the North East of England.Participants2950 NHS staff, of whom 43 took part in a telephone interview.Main outcome measuresPrevalence of bullying was measured by the revised Negative Acts Questionnaire (NAQ-R) and the impact of bullying was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
183
4
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(207 citation statements)
references
References 45 publications
12
183
4
8
Order By: Relevance
“…This rate is far higher than rates of bullying which have been estimated as only affecting 1-3% of doctors on a daily or weekly basis. 1 The data suggests that RDA communication encompasses a wide spectrum of behaviours, for which bullying is a subset of the wider problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate is far higher than rates of bullying which have been estimated as only affecting 1-3% of doctors on a daily or weekly basis. 1 The data suggests that RDA communication encompasses a wide spectrum of behaviours, for which bullying is a subset of the wider problem.…”
Section: Discussionmentioning
confidence: 99%
“…Destructive or negative workplace communication is recognised to be a problem both in the NHS and other organisations [1][2][3][4] and has attracted concern following recent care scandals such as Mid Staffordshire and Morecombe Bay. 5,6 Negative workplace behaviours encompass a broad spectrum and most of the research on negative communication between doctors has analysed bullying or undermining as a discrete subset.…”
Section: Introductionmentioning
confidence: 99%
“…exacerbate their psychological distress 49,50 . 60,74,75 , and/or pre-existing mental health conditions 60,75 .…”
mentioning
confidence: 99%
“…NHS (Carter et al, 2013) performed a workplace bullying survey in the UK NHS research and discovered that an overall 20 % of staff reported having been bullied by other staff to some degree and 43 % reported having witnessed bullying in the last 6 months. In addition, male staff and staff with disabilities reported higher levels of bullying.…”
Section: Adams (1992a)mentioning
confidence: 99%